Potensi padung-padung sebagai alternatif elemen estetik pada pengembangan desain produk kontemporer - Ariani Ariani (Institut Seni Indonesia Yogyakarta, 2017)
Karo tribe in North Sumatra as one of the ethnic variety in the archipelago has its own art and cultural heritage, one of which is a unique jewelry called padung-padung. This jewelry was used by Karo women in the past as jewelry as well as status symbol. Currently, padung-padung completely no longer used, even many Karo people, especially younger generation, do not know it. The strong influence of foreign culture due to the advancement of technology has become one of the reasons for the increasingly displaced padung-padung. This article is a summary of the result of previous research that aims to re-examine the existence of padung-padung in the past, identify the meaning and role and cause of the loss of padung-padung from the life of Karo tribe. In addition, this study also aims to explore the potential of padung-padung as an alternative aesthetic elements in the development of contemporary product design in order to preserve the diversity of art and culture of Indonesia.Keywords: padung-padung, nine elements of artifact forming, aesthetic element, contemporary product design